Explaining Sad People’s Memory Advantage for Faces - Hills, Peter J.; Marquardt, Zoe; Young, Isabel; Goodenough, Imogen (Frontiers in Psychology, 2017)
Sad people recognise faces more accurately than happy people (Hills, Werno, & Lewis, 2011). We devised four hypotheses for this finding that are tested between in the current study. The four hypotheses are: 1. sad people engage in more expert processing associated with face processing; 2. sad people are motivated to be more accurate than happy people in an attempt to repair their mood; 3. sad people have a defocused attentional strategy that allows more information about a face to be encoded; and 4. sad people scan more of the face than happy people leading to more facial features to be encoded. In Experiment 1, we found that dysphoria (sad mood often associated with depression) was not correlated with the face-inversion effect (a measure of expert processing) nor with response times but was correlated with defocused attention and recognition accuracy. Experiment 2 established that dysphoric participants detected changes made to more facial features than happy participants. In Experiment 3, using eye-tracking we found that sad-induced participants sampled more of the face whilst avoiding the eyes. Experiment 4 showed that sad-induced people demonstrated a smaller own-ethnicity bias. These results indicate that sad people show different attentional allocation to faces than happy and neutral people.